Fundamentals of Electro-Electronic Circuits - Nguyen Tien Dzung (Bach Khoa, 2010)
The book is addressed to students at Vietname universies of technology, wich offer electro- electronic and informatics majors for advanced education and internationl joint programs. In addition, this book could be used as a good reference for researchers, lectures and students interested in electro-electronics and its related application fields.It is the first volume of a set two books, which covers both basic theory and principles in the field of electro-electronic circuits along with typical applications.